Comparison of cysteine peptidase activities in Trichobilharzia regenti and Schistosoma mansoni cercariae - Kasný, M; Mikes, L; Dalton, J P; Mountford, A P; Horák, P (Parasitology, 2007)
Cercariae of the bird schistosome Trichobilharzia regenti and of the human schistosome Schistosoma mansoni employ proteases to invade the skin of their definitive hosts. To investigate whether a similar proteolytic mechanism is used by both species, cercarial extracts of T. regenti and S. mansoni were biochemically characterized, with the primary focus on cysteine peptidases. A similar pattern of cysteine peptidase activities was detected by zymography of cercarial extracts and their chromatographic fractions from T. regenti and S. mansoni. The greatest peptidase activity was recorded in both species against the fluorogenic peptide substrate Z-Phe-Arg-AMC, commonly used to detect cathepsins B and L, and was markedly inhibited (> 96%) by Z-Phe-Ala-CHN2 at pH 4.5. Cysteine peptidases of 33 kDa and 33-34 kDa were identified in extracts of T. regenti and S. mansoni cercariae employing a biotinylated Clan CA cysteine peptidase-specific inhibitor (DCG-04). Finally, cercarial extracts from both T. regenti and S. mansoni were able to degrade native substrates present in skin (collagen II and IV, keratin) at physiological pH suggesting that cysteine peptidases are important in the pentration of host skin.
Keywords: kolagen; Chromatography, Gel; diazomethan; inhibitory proteas; leucin; cysteinové endopeptidasy; Collagen; Keratins; koncentrace vodíkových iontů; Leucine; Diazomethane; Schistosomatidae; Cysteine Endopeptidases; Protease Inhibitors; Gelatin; gelová chromatografie; keratiny; Schistosoma mansoni; zvířata; Hydrogen-Ion Concentration; Binding Sites; vazebná místa; želatina; Animals